Research on Evaluation Index System of Smart City - Xiaojing Dong (Forest Chemicals Review)
With global economy development, people begin to take care of the quality of their life. "Smart City" is mentioned and paid great attention to by many different national governments and a lot of social organizations all over the world. In western countries, many specialists have researched it, in order to weight and evaluate people’s normal life. In China, it was focused on a little late. First, the author introduces experience of these west countries, such as GNP, IUP and ICF. Second, he analyzes the research situation in China smart cites now. In the end, the author thinks, it is essential to set up a complete set of smart city index evaluation system, in order to evaluate “Smart City” in China. The indicators in the system are selected should be appropriate, scientific, effective and comprehensive. The paper focuses on how to build and evaluate our smart city standardization. Studying on other countries experience and our policies, the author tries to put forward effective index system to evaluate our smart cities in China.